Efektivitas Pemberian Tablet Fe dan Tambahan Buah Pepaya California (Carica Pepaya L) Terhadap Peningkatan hemoglobin Pada Remaja Putri di Pondok Tahfidz Nurul Qur’an MAN 1 Kudus: Effectiveness of Fe Tablets and California Papaya Fruit Supplement (Carica Papaya L) on Hemoglobin Increase on Young Women at Pondok Tahfidz Nurul Qur'an MAN 1 Kudus - Nurul Kamila; Indah Puspitasari; Dwi Astuti (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Anemia remains a global health problem, with a prevalence of 29.9% among women aged 15–49 years according to the 2023 Basic Health Research. In adolescent girls, anemia is commonly caused by iron deficiency and the menstrual cycle. Efforts to enhance iron absorption can be supported by consuming iron tablets combined with vitamin C–rich sources, such as papaya. Objective: This study aimed to assess the effectiveness of iron tablets combined with papaya fruit (Carica papaya L.) in increasing hemoglobin levels among adolescent girls. Methods: The study employed a quasi-experimental design with two pre-test–post-test groups. Results: The t-test results showed a significant increase in hemoglobin levels in both groups (p < 0.05), with a mean difference of 0.58 g/dl higher in the intervention group than in the control group. Conclusion: These findings indicate that the combination of iron tablets and papaya fruit is more effective in increasing hemoglobin levels among adolescent girls at the Nurul Qur'an MAN 1 Kudus Tahfidz boarding school.